Commissioning and quality assurance of Euromechanics add-on multileaf collimator. (21st December 2020) - Rohani, Seyed Aliasghar; Mahdavi, Seied Rabi; Mostaar, Ahmad; Rahimi, Shaghayegh; Mohammadi, Reza; Geraily, Ghazale
Abstract: In this study, the beam characteristics of a Euromechanics add-on MLC that has been installed on a Varian CLINAC 2100 C/D linear accelerator are presented. This was the first installation of 60-leaf PMLC from Euromechanics Company worldwide and all mechanical and dosimetric parameters were measured before clinical use of this kind of MLC. Mechanical tests were executed for different gantry and collimator angles. Leaf position accuracy and leaf gap reproducibility were checked with four different tests. The leaf transmissions, collimator (Sc), phantom (Sp), total (Sc, p) scatter factors, output of the machine, beam profiles for off-axis ratios, central axis depth dose, flatness, symmetry and penumbra have been measured for different field sizes pre and post MLC installation in 6 and 18 MV-mode. To evaluate the effect of new data on clinical plans, different beam setup configurations conformed with MLC and custom blocks were planned on CT images of thorax a CIRS phantom model 002LFC in the same treatment planning system. Leaf position in picket fence test found to be in range between 4.89–5.02 cm instead of nominal 5 cm, however the results of this test with EPIDs image and PIPSpro software showed the higher deviation rather than the results reported from the tests with EBT3 films. The measured data showed that on average Sc, p and Sc were increased 0.22% (P = 0.86) and 0.34% (P = 0.86) for 6 MV and 0.37% (P = 0.84) and 0.42% (P = 0.88) for 18 MV beams for different field sizes, respectively. Good agreement was observed between the PDD and profile curves pre and post MLC installation that was expected based on no changes in beam energy and geometry of the collimators. Based on the mechanical and dosimetry results which have been achieved from our different standard tests, it was found no significant differences between pre and post MLC installation values. This indicates, installation and using this system is clinically acceptable.